Pengaruh Suhu dan Waktu Ekstraksi Terhadap Kandungan Flavonoid dan Aktivitas Antioksidan Daun Sirsak (Annona muricata L.) Menggunakan Ultrasonik - Ayuk Yuliantari, Ni Wayan; Rai Widarta, I Wayan; Mayun Permana, I Dewa Gede (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 4 No 1 (2017), 2017)
This research was conducted to determine temperature and time exraction effect onflavonoid content and antioxidant activity of soursoup leaf extract. The experimental designused in this research was a factorial completely randomized design which consisted of twofactors. The first factor was temperature of extraction that consists of temperature 35C,45oC, and 55oC. The second factor was the time of extract namely 10, 20, and 30 minuts.The treatment was repeated twice to obtain 18 units of the experiment. Data were analyzedwith analysis of variance, followed by Duncan test. The results showed that the besttreatment of soursoup leaf extract temperature of 450C and extraction time 20 minutesresulted in yield 19.14%, total flavonoids 903.90 mgQE /g extract and IC 50 value was 258.155 mg / L.
Keywords: soursoup leaf; ultrasonic; , flavonoid; antioxidant activity